Feeding practices and nutritional status of infant and young children on coastal and inland areas if the Fourth District of Camarines Sur, Philippines - Manrique, Jeena Sandra R.; dela Luna, Kim Leonard G.; Rodriguez, Anna Paulina S.; Rama-Sabandal, Raycha; Sy, Alvin Duke R.; Guirindola, Mildred O. (Manila College of Public Health, University of the Philippines Manila, 2024)
IYCF practices significantly impact growth, development in early childhood, and long-term health status. This study investigates IYCF practices and the nutritional status of children aged 0-23 months in the fourth district of Camarines Sur. A total of 628 households with children aged 0-23 months participated in an analytical cross-sectional study employing a two-staged stratified random sampling design. Data on sociodemographic, economic factors, and IYCF practices were collected. Moreover, weight and length of the IYC were evaluated using the WHO Anthro Plus software. Descriptive statistics and multiple logistics regression were used in the analysis using R statistical software version 4.3.1.

This study showed that the prevalence of stunting (42.8%) was of very high public health significance, wasting (14.8%) was of high significance and underweight (12.9%) was of medium severity in the study areas. Furthermore, 98.9% of infants were breastfed, while eight out of 10 children (82.6%) consumed unhealthy foods. Moreover, none of the IYCF practices were found to be associated with these undernutrition indices. Among infants aged 0.01-5.99, educational attainment of mothers (aOR=0.26; p=0.03), age in months (aOR=0.77; p=0.01), and poor income households (aOR=40; p=0.02) were associated with stunting. On the other hand, poor income households (aOR=0.25; p=0.02) were associated with underweight. Lastly, infants who experienced illness in the past month (aOR=0.32; p=0.03) were associated with wasting.
Among IYC aged 6.00-23.99 months, the age of the child in months (aOR=1.09; p<0.00) and the sex of the child (aOR=1.55; p=0.03) were associated with stunting. Children who experienced illness in the past month (aOR=2.21; p=0.01) and mothers with no formal education (aOR=13.36; p=0.04) were significantly associated with underweight. Similarly, wasting was associated with both past illness (aOR=2.20; p=0.01) and mothers with no formal education (aOR=12.53; p=0.04).
After adjusting for potential confounders, there was no significant association found between the IYCF indicators and the nutritional status of the children. Thus, it can be emphasized that undernutrition was a multifactorial condition influenced by various factors such as maternal education, age and sex of the child, socio-economic status, frequency of illness.
Includes references and appendices.
Thesis
Keywords: Infants -- Nutrition -- Philippines -- Camarines Sur (Fourth District); Children -- Nutrition -- Philippines -- Camarines Sur (Fourth District); Child nutrition -- Philippines -- Camarines Sur (Fourth District); Infant feeding -- Philippines -- Camarines Sur (Fourth District)